2011
DOI: 10.1111/j.1365-2982.2011.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of interstitial cells of Cajal in the generation and modulation of motor activity induced by cholinergic neurotransmission in the stomach

Abstract: Pacemaker ICC play a prominent role in the expression of motor activity induced by cholinergic activity and our data suggest that cholinergic neurotransmission to ICC affects the pacemaker frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 52 publications
3
37
1
Order By: Relevance
“…There has been a long standing controversy whether ICC have a role in the regulation of excitatory and inhibitory neurotransmission, besides generating slow waves [8][9][10][11][12][13][14][15][16]26 . In small intestinal circular smooth muscle cells, ongoing slow waves with a frequency of B30-35 cycles per min (Fig.…”
Section: Icc Depletion Blocks Excitatory Enteric Neurotransmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a long standing controversy whether ICC have a role in the regulation of excitatory and inhibitory neurotransmission, besides generating slow waves [8][9][10][11][12][13][14][15][16]26 . In small intestinal circular smooth muscle cells, ongoing slow waves with a frequency of B30-35 cycles per min (Fig.…”
Section: Icc Depletion Blocks Excitatory Enteric Neurotransmissionmentioning
confidence: 99%
“…Previous studies provided clear evidence that ICC generate a rhythmic pacemaker current, which manifests itself as slow waves in the membrane potential of smooth muscle cells, resulting in rhythmic bowel contractions 4,7,8 . However, a role of ICC in the transmission of excitatory and inhibitory signals from enteric neurons to smooth muscle cells is highly controversial and remains an outstanding question [8][9][10][11][12][13][14][15][16] . This is mainly because of the general lack of models and systems to study ICC function in adult animals at genetic level 9,11,16 .…”
mentioning
confidence: 99%
“…Other studies have shown the degree of stretch of smooth muscle may influence the contractile forces generated in the antrum of rats [15]. Whether or not fibrosis is a useful surrogate for clinical pyloric dysfunction is unknown as there are no data correlating the presence or degree of fibrosis with meaningful clinical standards or metrics of gastric emptying.…”
Section: Degree Of Fibrosismentioning
confidence: 99%
“…Whether neuronal input to ICC is significant is a matter of debate, [1][2][3][4][5][6][7]17,26 however growing evidence suggests that ICC play a role in enteric neurotransmission. It has been shown that intramuscular ICC is closely associated with myenteric motor neurons, forming synapse-like junctions with nerve varicosities.…”
Section: Gastrointestinal Motilitymentioning
confidence: 99%